Mechanism of adenylate cyclase activation through the beta-adrenergic receptor: catecholamine-induced displacement of bound GDP by GTP. - Cassel, D (1978)
The fate of the guanyl nucleotide bound to the regulatory site of adenylate cyclase was studied on a preparation of turkey erythrocyte membranes that was incubated with [3H]GTP plus isoproterenol and subsequently washed to remove hormone and free guanyl nucleotide. Further incubation of this preparation in the presence of beta-adrenergic agonists resulted in the release from the membrane of tritiated nucleotide, identified as [3H]GDP. The catecholamine-induced release of [3H]GDP was increased 2 to 3 times in the presence of the unlabeled guanyl nucleotides GTP, guanosine 5'-(beta,gamma-imino)triphosphate [gpp(NH)p], GDP, and GMP, whereas adenine nucleotides had little effect. In the presence of Gpp(NH)p, isoproterenol induced the release of [3H]GDP and the activation of adenylate cyclase, both effects following similar time courses. The findings indicate that the inactive adenylate cyclase possesses tightly bound (GDP, produced by the hydrolysis of GTP at the regulatory site. The hormone stimulates adenylate cyclase activity by inducing an "opening" of the guanyl nucleotide site, resulting in dissociation of the bound GDP and binding of the activating guanosine triphosphate.